Perhiasan Tradisional Suku (di) Sarmi dan Suku Momuna Papua : Pendekatan Etnoarkeologis - Rini Maryone (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
One of the cultural heritage of the ethnic groups in Papua is traditional jewelry. This traditional jewelry is quite unique to use, with the uniqueness of the jewelry made of beads, seeds, animal fangs, noken, and traditional clothes which are also made of bark with Papuan motifs. Therefore, this study aims to highlight cultural artifacts in the form of traditional jewelry on ethnic groups in Papua, especially in the North Coast of Sarim Regency and the Central Mountains of Yahukimo Regency, Papua. This research uses an ethnoarcheological approach which is carried out in two stages, namely data collection and data processing. Data collection is done in several ways, namely: surveys, interviews and conducting literature studies. The results of the research show that there are differences in the use of traditional jewelry between the Sarmi tribe in the northern coastal region and the Momuna tribe in Yahukimo Regency, the Central Mountains of Papua. Because this really depends on the values contained in the jewelry and its function in the culture of each tribe.